The wi-fi experience : - Davis, Harold (Que, 2002)
This book is a complete "experience" for Wi-Fi users, offering how-to instructions and software discounts, full versions on the CD, and recommendations for Wi-Fi projects. The author takes the reader beyond just wireless networking to explore Wi-Fi capabilities in real-world applications such as Wi-Fi with PDAs, VOIP, and building your own Wi-Fi phone